Don't know much about The universe : - Davis, Kenneth C. (Random House, Inc, 2001)
Don't know much about the Universe uses the now-familiar and popular question-and-answer format to inform and entertain listeners by examining a subject that has inspired the greatest of fascinations, produced many popular misconceptions, ultimately helped to shape the course of history.